Campus Wellness Program Evaluation: Effectiveness of a Brief Psychoeducation Intervention for Wellness Promotion - James Beauchemin; Michelle Ihmels; Danya Krueger; Christopher McGrath (The Ohio State University Libraries, 2024)
Background: College students are experiencing high levels of stress and compromised well-being, compounded by sedentary lifestyle and risky behaviors. In response to these challenges, college campuses are offering a variety of wellness programming intervention opportunities. Aim: This research study examined the effectiveness of a brief psychoeducational intervention on perceptions of stress, wellness, mental health, and life satisfaction. Methods: The study utilized a longitudinal, explanatory mixed methods design, with random assignment. To augment quantitative data, brief, semi-structured interviews were completed with 13 study participants post-intervention. Results: Results of repeated-measures analysis of variance (RM-ANOVA) demonstrated no significant between-group differences. Intervention group pair-wise comparisons revealed positive trends across time for several outcome variables. Applied Thematic Analysis (ATA) revealed four primary themes including: stress-reduction benefits of relaxation techniques, improved knowledge of health impacts of alcohol, increased intentionality regarding nutrition habits, and need for increased accessibility of wellness programming. Conclusions: This study provides insight into the strengths and limitations of brief psychoeducation interventions in facilitating lifestyle change among college students. Implications for campus wellness programming are discussed.